On a syntactically defined invariant of symbolic dynamics - Krieger, Wolfgang (Ergodic theory and dynamical systems, 2000)
A partially ordered set that is invariantly associated to a subshift is constructed. A property of subshifts, also an invariant of topological conjugacy, is described. If this property is present in a subshift then the constructed partially ordered set is a partially ordered semigroup (with zero). In the description of these invariants the notion of context is instrumental.